Greater Protein Intake at Breakfast or with Snacks and Less at Dinner Is Associated with Improved Metabolic Health in US Adults (P18-003-19). (13th June 2019) - Berryman, Claire; Lieberman, Harris R; Fulgoni, Victor; Pasiakos, Stefan
Abstract: Objectives: Greater protein intakes have been associated with decreased weight, BMI, waist circumference (WC) and increased HDL-cholesterol (HDL-C) concentrations. However, the relationship between protein intake during specific eating occasions and metabolic health is not well described. This study measured protein intake at meals (breakfast, lunch, dinner) and snacks and evaluated associations between protein intake at meals or snacks and markers of metabolic health in US adults. Methods: Using the National Cancer Institute method, deciles of individual usual intake (IUI) for protein at meals and combined snacking occasions were calculated using NHANES 2013–2016 data ( n  = 10, 112; ≥19 y). Relationships between protein intake at meals and snacks and markers of metabolic health were determined using regression analysis. Covariates included age, age 2, sex, ethnicity, physical activity level, poverty income ratio, IUI of carbohydrate at specific meal/snack, IUI of total fat at specific meal/snack, BMI (non-weight-related variables), and IUI of protein at other meals/snacks. P  < 0.01 was considered significant. Results: Deciles of protein intake ranged (10 th and 90 th percentiles, mean ± SE) from 5.9 ± 0.1 to 22.6 ± 0.3 g/d at breakfast, 14.0 ± 0.1 to 34.6 ± 0.4 g/d at lunch, 24.3 ± 0.3 to 46.8 ± 0.2 g/d at dinner, and 4.9 ± 0.1 to 16.5 ± 0.2 g/d at snacking occasions. Greater protein intake at breakfast was positively related to HDL-C (0.51 ± 0.17 mg/dL per decile, P  = 0.004). Protein intake at dinner was positively associated with the homeostatic model assessment of insulin resistance (0.23 ± 0.08 per decile, P  = 0.008). Protein intake from snacks was inversely associated with diastolic blood pressure (−0.27 ± 0.09 mm Hg per decile, P  = 0.004) and positively associated with HDL-C (0.68 ± 0.20 mg/dL per decile, P  = 0.002). Protein intakes at meals and snacks were not associated with BMI, WC, systolic blood pressure, insulin, glucose, total cholesterol, LDL-cholesterol, triglycerides, or CVD risk. Conclusions: In US adults, consuming greater protein at breakfast or with snacks and less protein at dinner may be related to improved metabolic health. Funding Sources: The views expressed herein are those of the authors and do not reflect official policy of the Army, DoD, or U.S. Government. Supported by DMRP/USAMRMC.